2001
DOI: 10.1002/nme.190.abs
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of hybrid active–passive vibration damping of multilayer piezoelectric sandwich beams—part II: System analysis

Abstract: SUMMARYAn electromechanically coupled ÿnite element model has been presented in Part 1 of this paper in order to handle active-passive damped multilayer sandwich beams, consisting of a viscoelastic core sandwiched between layered piezoelectric faces. Its validation is achieved, in the present part, through modal analysis comparisons with numerical and experimental results found in the literature. After its validation, the new ÿnite element is applied to the constrained optimal control of a sandwich cantilever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In the case of quadratic electric potential distribution, a diagonal electric permittivity tensor and piezoelectric component P 133 ¼ 0, which is the case for a major class of piezoceramics [31] and, specifically, the ones used in piezoelectric beam literature [6,10,5,1,3,8,9,21], the three differential Eq. (57) take the form,…”
Section: Quadratic Electric Potential Distribution Within the Cross Smentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of quadratic electric potential distribution, a diagonal electric permittivity tensor and piezoelectric component P 133 ¼ 0, which is the case for a major class of piezoceramics [31] and, specifically, the ones used in piezoelectric beam literature [6,10,5,1,3,8,9,21], the three differential Eq. (57) take the form,…”
Section: Quadratic Electric Potential Distribution Within the Cross Smentioning
confidence: 99%
“…Along the same lines, Koutsawa [23] attempts to solve the problem of static piezoelectric beams by using higher order displacement theories for beams. This paper aims to present a simple three-dimensional finite element framework for linear piezoelectric beams, derived from first principles, in order to bridge the gap between existing simplified lumped or distributed parameter models [1,6,[8][9][10]12,13] and the most sophisticated nonlinear warping beam models [19][20][21][22][23]. In the process, interesting new physical magnitudes, such as the coupled shear or the coupled bending/torsional moment introduced as a result of an electric displacement, will naturally arise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, few studies focus on the optimization of this coupling for given structure and piezoelectric material. In particular, it has been shown that piezoelectric actuators using their thickness-shear mode can be more effective than surface-mounted extension piezoelectric actuators for both active Raja, Prathap and Sinha, 2002;Baillargeon and Vel, 2005;Trindade and Benjeddou, 2006) and passive (Benjeddou and Ranger-Vieillard, 2004;Benjeddou, 2007;Trindade and Maio, 2008) vibration damping. One of the reasons for that is the thicknessshear electromechanical coupling coefficient k 15 that is normally twice the value of the extension one, k 31 , which may lead to a higher effective electromechanical coupling coefficient (Trindade and Benjeddou, 2009).…”
Section: Introductionmentioning
confidence: 99%